The Alethic Status of Contradictions in Fictional Discourse - Vladimir Vujošević (Organon F, 2024)
Whether contradictions could be “true in fiction” has become an unavoidable topic in the debates on the bounds of fictionality. This paper claims that genuine contradictions in fiction are far more infrequent phenomena than is usually claimed. The majority of cases that have been put forward as examples of contradictory fictions can be convincingly understood either as instances of rhetorical pseudo-contradictions or (in the case of the so-called “forking-path“ narratives) as disjunctions of possible outcomes rather than contradictory conjunctions of simultaneously enacted exclusive scenarios. The only philosophically interesting category of contradictory fiction would be the one in which a single “root” contradiction is explicitly affirmed as the central element of the story (in the third-person, authoritative narrative voice). The paradigmatic example would be the revised version of Graham Priest’s “Sylvan’s Box” this paper presents. However, it could be argued that the problem with such narratives is that they unsuccessfully attempt to perceptually code what remains exclusively propositional content. They are, thus, fatally under-described, and the truth of the contradictory proposition fails to be adequately established in fiction. The idea that one can posit contradictions as fictional facts is based on oversimplified notions of narrative conventions and truth in fiction.